2011
DOI: 10.1183/09031936.00105110
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cigarette smoke and hypoxia on pulmonary circulation in the guinea pig

Abstract: Cigarette smoke (CS) and chronic hypoxia (CH) can produce pulmonary hypertension. Similarities and differences between both exposures and their interaction have not been explored. The aim of the present study was to investigate the effects of CS and CH, as single factors or in combination, on the pulmonary circulation in the guinea pig.51 guinea pigs were exposed to CS for 12 weeks and 32 were sham-exposed. 50% of the animals in each group were additionally exposed to CH for the final 2 weeks. We measured pulm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
47
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(53 citation statements)
references
References 36 publications
4
47
1
1
Order By: Relevance
“…Whereas typical plexiform lesions from idiopathic PAH are only rarely described in COPD, up to 70% of patients with COPD go on to develop PAH and pulmonary artery remodeling, features directly associated with worse prognosis and disease exacerbations (27). In addition, our results support findings in vivo of effects of smoking on pulmonary vasculature remodeling even in the absence of airspace destruction (28).…”
Section: Discussionsupporting
confidence: 79%
“…Whereas typical plexiform lesions from idiopathic PAH are only rarely described in COPD, up to 70% of patients with COPD go on to develop PAH and pulmonary artery remodeling, features directly associated with worse prognosis and disease exacerbations (27). In addition, our results support findings in vivo of effects of smoking on pulmonary vasculature remodeling even in the absence of airspace destruction (28).…”
Section: Discussionsupporting
confidence: 79%
“…Whereas guinea-pigs exposed to CS showed increased mPAP and RV hypertrophy compared with nonexposed animals, in keeping with previous studies [22,23]; CS-exposed, sildenafil-treated animals displayed mPAP values and a RV/LV+S weight ratio similar to the nonexposed animals, confirming the vasodilator action of sildenafil in this experimental model [10][11][12]. The lack of increase in PAP was not accompanied by differences in lung vessel structure, since CS-exposed guinea-pigs treated with sildenafil showed pulmonary artery wall thickening, muscularisation of small vessels and proliferation of smooth muscle cells at similar levels to CS-exposed, untreated guinea-pigs and at significantly higher levels than in nonexposed animals.…”
Section: Discussionsupporting
confidence: 78%
“…It is conceivable that the effect of CS exposure on pulmonary vessel structure could exceed those produced by hypoxia, which has been used in previous experimental settings. In fact, in a previous study conducted in guinea-pigs we showed differences in the characteristics of pulmonary vascular remodelling between CS exposure and hypoxia [23]. These current observations of sildenafil in the guinea-pig chronically exposed to CS contrast with the effects recently found in this experimental model using a sGC stimulator (BAY 41-2272) [18].…”
Section: Discussioncontrasting
confidence: 55%
“…Pulmonary endothelial dysfunction and vascular remodeling are also reported in the lungs of COPD patients (12,40,62). CS is a major risk factor for COPD (53).…”
Section: Discussionmentioning
confidence: 95%
“…It is well documented that CS causes systemic endothelial dysfunction in humans (39) and endothelial dysfunction in the pulmonary circulation in human and animal models (12,40,62). One important function of the pulmonary endothelium is maintenance of vascular barrier function.…”
mentioning
confidence: 99%